(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the current tasks before the technical science of general secondary schools and the psychological, pedagogical and technical-technological aspects of the educational process, the use of interdisciplinary links in the educational process, and the general secondary education. Many organizational, legal and scientific research works are being carried out on reforming the system, improving teaching technologies, forming modern knowledge and skills in students, using new teaching methods for this purpose. Through this, it is aimed to create a system of training a generation of competitive and high-potential personnel. This makes the formation of creativity-related skills in students one of the urgent tasks. That’s why, on the basis of innovative tools, thoughts and opinions about the need to develop creative abilities in young people have been discussed.